To add two species belonging to diaptomidae family to the fauna of inland freshwater crustaceans (Calanoida - Copepoda) of Vietnam - Hai, Ho Thanh; Luong, Tran Duc; Anh, Le Hung (Academia Journal of Biology, 2014)
Based on analysis of many samples collected from Day river (tributary of the Red river system), two species of Calanoida: Sinodiaptomus sarsi (Rylov, 1923) and Dolodiaptomus spinicaudatus Shen et Tai, 1964 that are firstly recorded in Vietnam. These species are described in detail in the paper. Up to now, 35 species of inland freshwater Calanoida-copepods are recorded in Vietnam. Among these, 25 species of Diaptomidae family. Dolodiaptomus spinicaudatus was firstly descripted (Shen et Tai, 1964). In China, this species distributed only in Yunnan, now found in north Vietnam. Sinodiaptomus sarsi originated from temperate area, can largely distributed from Asia Eastern and Western countries to the subtropical part in southeast China and nowaday this species was found in north Vietnam. Therefore, this species can extensively distributed from Russia, Mongolia, Korea, Japan and China to north Vietnam. However, south-distributed area of this species only limited to north Vietnam, and found only in winter-spring season with lower temperature.